A Coach's Guide to Maximizing the Youth Sport Experience Work Hard, Be Kind. - Fry, Mary.; Gano-Overway, Lori A.; Guivernau, Marta; Kim, Mi-Sook.; Newton, Maria (Milton : Routledge, 2019)
This book guides sport coaches, parents and administrators in creating a caring and task-involving sport climate that helps athletes perform their best and have an enjoyable and meaningful sport experience. It introduces the concept of a caring and task-involving climate and provides a "how to" guide to creating this climate in sport. Firstly, this guide introduces the caring and task-involving climate and summarizes research highlighting its many benefits. Secondly, the five features of this climate are presented along with the reflective exercises for developing them within a team. Coaches will see strategies in action, sample conversations, and a variety of ways to implement the features of a caring and task-involving experience. By describing how it may be implemented and methods for overcoming possible challenges, this book finally highlights how parents and sport administrators can support the creation and preservation of caring and task-involving climates. By helping teams develop caring climates that optimize athletes' sport experience and performance, this book is essential reading for coaches, sport administrators, parents, and sport psychology practitioners. It will also be of great interest to those who have minimal training in sport psychology, but who are involved in sport at many levels, such as youth and high school.
Why Teach Athletes that Mistakes are Part of Learning?Understanding Why Athletes Make Mistakes,Making Mistakes Part of Learning; Helping Athletes Buy into the Philosophy that Mistakes are Part of Learning; When is Punishment Appropriate to Use?; Reflecting on Practice; Responding to Mistakes: Observing My Coaching Responses; Communities of Practice; Sources; 6 Features of a Caring and Task-Involving Climate in Sport: Every Athlete Plays an Important Role on the Team; Highlights; Identifying and Communicating the Important Contributions that Each Athlete Makes to the Team,*****
Description based upon print version of record.
Reflecting on Practice
OCLC-licensed vendor bibliographic record.
Keywords: PSYCHOLOGY / General; Sports for children -- Coaching; Sports for children